The Social Equality of Children with Special Needs in Mataram - Astrit Maria (Universitas Muhammadiyah Mataram, 2018)
While disability is treated socially equal in most western countries, the prejudice that Asians adhere to traditional cultural view related to curse, bad luck, and humiliation is really strong. In fact, attitudes toward the handicapped strongly refer to social as well as cultural construction built in society. Hence, this research was conducted to discover how Mataram natives truly treat child with special education needs in the social interactions within school setting using qualitative approach and engaging observation as well as video recordings as data collection methods. The findings confirm that destructive treatment does not occur among Mataram disabled and non-disabled peers despite the existing prejudice. Moreover, constructive treatment from the community builds the child’s self-esteem in public setting stronger.